Nerve growth factor locally sensitizes nociceptors in human skin - Obreja, Otilia; Rukwied, Roman; Schmelz, Martin (Pain, 2018)
Nerve growth factor (NGF) injected into the human skin causes local hyperalgesia to mechanical and electrical stimuli lasting for weeks. Pig data suggested axonal sensitization of C-nociceptors as a contributing mechanism. Here, we recorded single C-nociceptors in 11 human subjects 3 weeks after intracutaneous injection of 1 μg NGF into the foot dorsum. For each identified unit, the receptive field was mapped and, whenever possible, we recorded 2 terminal branches of the same unit, 1 from the hyperalgesic NGF-site (“inside”) and the other from the nonsensitized skin (“outside”). In the saline-treated control feet, mechano-insensitive nociceptors (CMi) were more abundant than at the NGF sites (36% vs 19%). Units with axonal properties of CMi fibres but displaying positive mechanical responses (“CMi-like”) dominated at the NGF site (27% vs 6%). Moreover, axonal branches innervating the hyperalgesic skin displayed significantly lower electrical thresholds and less activity-dependent conduction velocity slowing when compared with “outside” or control skin. The “inside” branches also showed long-lasting after-discharges and less adaptation to repeated mechanical stimuli. NGF-induced long-term nociceptor hyperexcitability was maximum at the terminal branches directly treated with NGF. The sensitization included sensory and axonal components affecting both activation thresholds and supra-threshold responses. Our data suggest that a combination of sensory sensitization and axonal hyperexcitability is underlying the localized hyperalgesia by facilitating action potential generation and conduction. Axonal changes were also found in the asymptomatic skin surrounding the NGF-treatment sites, thereby possibly reflecting “nociceptive priming.”